Observation of roton mode population in a dipolar quantum gas - Chomaz, L.; van Bijnen, R. M. W.; Petter, D.; Faraoni, G.; Baier, S.; Becher, J. H.; Mark, M. J.; Wächtler, F.; Santos, L.; Ferlaino, F. (Nature physics, 2018)
The concept of a roton, a special kind of elementary excitation forming a minimum of energy at finite momentum, has been essential for the understanding of the properties of superfluid 4 He (ref. 1 ). In quantum liquids, rotons arise from the strong interparticle interactions, whose microscopic description remains debated 2 . In the realm of highly controllable quantum gases, a roton mode has been predicted to emerge due to magnetic dipole–dipole interactions despite their weakly interacting character 3 . This prospect has raised considerable interest 4 – 12 ; yet roton modes in dipolar quantum gases have remained elusive to observations. Here we report experimental and theoretical studies of the momentum distribution in Bose–Einstein condensates of highly magnetic erbium atoms, revealing the existence of the long-sought roton mode. Following an interaction quench, the roton mode manifests itself with the appearance of symmetric peaks at well-defined finite momentum. The roton momentum follows the predicted geometrical scaling with the inverse of the confinement length along the magnetization axis. From the growth of the roton population, we probe the roton softening of the excitation spectrum in time and extract the corresponding imaginary roton gap. Our results provide a further step in the quest towards supersolidity in dipolar quantum gases 13 . The roton energy spectrum, originally introduced by Landau, explains the thermodynamic behaviour of strongly interacting liquid helium at low temperature. Now, a similar spectrum has been observed in weakly interacting dipolar quantum gas.